1968
DOI: 10.1182/blood.v32.3.376.376
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Erythropoiesis XXII. Erythropoietin Production in the Newborn Animal

Abstract: Erythropoietin production was examined in the newborn rat. Even though there was significant anemia present during the early neonatal phase of life in the rat, erythropoietin could not be demonstrated in the plasma. Exposure to simulated levels of altitude of 23,000 feet for a period of 18 hr. resulted in the production of demonstrable levels of erythropoietin in the plasma. The amount of erythropoietic activity which could be demonstrated in the plasma of hypoxic animals increased with age from values of 0.76… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1969
1969
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Erythropoietin appears necessary for the production of recognizable erythroid cells in the adult mouse (Bleiberg, Liron & Feldman 1967;Curry, Trentin & Wolf 1967;Schooley 1967). However, the haematologic response of neonatal rodents, such as mice and rats, to anaemia, starvation, hypoxia, or nephrectomy (treatments which influence erythro poietin production in adult rodents) differs from that of adult animals subjected to similar treatment (Lucarelli et al 1968;Lucarelli & Butturini 1967;Carmena, Howard & Stohlman 1968;Stohlman 1970). During early neonatal life the response of the young rodents becomes progressively more similar to that of adult animals (Carmena et al 1968, Stohlman 1970.…”
Section: (B) Erythropoiesis In the Developing Mouse Embryomentioning
confidence: 99%
See 1 more Smart Citation
“…Erythropoietin appears necessary for the production of recognizable erythroid cells in the adult mouse (Bleiberg, Liron & Feldman 1967;Curry, Trentin & Wolf 1967;Schooley 1967). However, the haematologic response of neonatal rodents, such as mice and rats, to anaemia, starvation, hypoxia, or nephrectomy (treatments which influence erythro poietin production in adult rodents) differs from that of adult animals subjected to similar treatment (Lucarelli et al 1968;Lucarelli & Butturini 1967;Carmena, Howard & Stohlman 1968;Stohlman 1970). During early neonatal life the response of the young rodents becomes progressively more similar to that of adult animals (Carmena et al 1968, Stohlman 1970.…”
Section: (B) Erythropoiesis In the Developing Mouse Embryomentioning
confidence: 99%
“…However, the haematologic response of neonatal rodents, such as mice and rats, to anaemia, starvation, hypoxia, or nephrectomy (treatments which influence erythro poietin production in adult rodents) differs from that of adult animals subjected to similar treatment (Lucarelli et al 1968;Lucarelli & Butturini 1967;Carmena, Howard & Stohlman 1968;Stohlman 1970). During early neonatal life the response of the young rodents becomes progressively more similar to that of adult animals (Carmena et al 1968, Stohlman 1970. Similarly, the supression of erythroid colony formation in the spleens of lethally irradiated, plethoric mice injected with liver cell suspensions prepared from 12-to 19-day foetal mice was only partial (Bleiberg & Feldman 1969).…”
Section: (B) Erythropoiesis In the Developing Mouse Embryomentioning
confidence: 99%
“…In adult animals the erythropoietic activity is not linked to the level of H b per se, but is mainly regulated through renal erythropoietin production, in response to changes in the 0, tension in 0,-sensing regions in the kidney (Fisher 1983). The 0,-dependent regulatory mechanism seems to be established already during fetal life (Finne 1968, Meberg 1980, H l g i & Kristiansen 1981, Thomaset al 1983, but partoftheerythropoietin production is extra-renal (Zanjani et al 1977, HHgl & Kristiansen 1981.…”
Section: Discussionmentioning
confidence: 99%
“…14 Later, the liver was identified as an additional extrarenal EPO source. [15][16][17][18][19][20][21][22] Most clinical observations supported the importance of the kidneys for erythropoiesis with complete erythroblastopenia in anuric renal failure patients 23 and after nephrectomy, 24 and polycythemia in patients with renal pathologies, such as renal cysts, hypernephroma, or hydronephrosis. [25][26][27][28][29][30][31][32][33] In the 1970s, EPO was isolated from the urine of anemic patients [34][35][36] followed by cloning and recombinant expression a decade later.…”
Section: Historic Perspective Of Hif Discoverymentioning
confidence: 99%
“…The investigators observed that bilateral nephrectomy abrogated the erythropoietic effect of CoCl 2 in rats and rabbits 14 . Later, the liver was identified as an additional extrarenal EPO source 15–22 . Most clinical observations supported the importance of the kidneys for erythropoiesis with complete erythroblastopenia in anuric renal failure patients 23 and after nephrectomy, 24 and polycythemia in patients with renal pathologies, such as renal cysts, hypernephroma, or hydronephrosis 25–33 .…”
Section: Historic Perspective Of Hif Discoverymentioning
confidence: 99%